2013
DOI: 10.1111/jace.12375
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of Multilayered Porous Structures: Part I‐Constitutive Models

Abstract: Theoretical analyses of shrinkage and distortion kinetics during sintering of bilayered porous structures are carried out. The developed modeling framework is based on the continuum theory of sintering; it enables the direct assessment of the cofiring process outcomes and of the impact of process controlling parameters. The derived "master sintering curve"-type solutions are capable of describing and optimizing the generic sintering shrinkage and distortion kinetics for various material systems. The approach u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…If there was no effect of gravity on the development of the distortions, all the three bilayer systems should have shown the same evolutions of curvatures. This is because the internal stresses balance over the thickness of the layers which makes the curvature to be affected only by the thicknesses in addition to the material properties . However, it is observed that the curvature varies depending on the length of the samples where less curvature is shown as the length of the sample increases because of gravity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…If there was no effect of gravity on the development of the distortions, all the three bilayer systems should have shown the same evolutions of curvatures. This is because the internal stresses balance over the thickness of the layers which makes the curvature to be affected only by the thicknesses in addition to the material properties . However, it is observed that the curvature varies depending on the length of the samples where less curvature is shown as the length of the sample increases because of gravity.…”
Section: Resultsmentioning
confidence: 99%
“…Sometimes the viscous parameters of the porous body are measured and reported in terms of the uniaxial viscosity, η u , and viscous Poisson's ratio,ν v , as:normalηnormalu=18normalη0ψφ6ψ+φandnormalνnormalv=3ψφ6ψ+φ…”
Section: Model Developmentmentioning
confidence: 99%
See 3 more Smart Citations